Perkaitan pengamalan etika kerja menurut perspektif Islam dengan kepuasan kerja guru di Maktab Rendah Sains MARA - Mohd Shahril, Ahmad Razimi (2012)
The Objective of the study is to investigate the relation between working ethics in accordance to the Islamic perspective and job satisfaction among MARA Junior Science Colleges (MJSC) teacher’s in Malaysia. Work ethics according to the islamic perspective refers to the values, norms and manners that which are throughly discussed by perminent scholars such as Al-Imam al-Ghazali, Ibn Maskaweyh, AI-Farabi, al-Raghib al-Isfahani, which are also seen as ‘ibadah’ (ritual performed to obtain blessing and love from Allah S.W.T) in Islam. Job Satisfaction refers to the 59 items previously developed by other researchers to measure job satisfaction when one aims to work to obtain love and blessing from god. To ensure the validity and reliability of the study, a variety of methods were applied in the study, quantitative datas were obtained through questionairres based on the results of previous studies, administered by research sample of 363 MJSC’s teachers and 12 principals selected were interviewed and observed. In order to simplify the data gathering process, Islamic working ethics perspective that can be categorized into 17 items had a signiﬁcant relationship to teacher’s job satisfaction at MARA Junior Science Colleges in Malaysia. The study also revealed the inﬂuence of demographic factors such as age, gender, salary and emolumens, work promotion received had a signiﬁcant relationship with Islamic work ethics and MJSC teacher’s job satisfaction. This study also showed that the major contribution of correlation between Islamic work ethics and job satisfaction is peer relationship.